The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1115/1.4028628
|View full text |Cite
|
Sign up to set email alerts
|

A Damage Mechanics Approach to Simulate Butterfly Wing Formation Around Nonmetallic Inclusions

Abstract: Nonmetallic inclusions such as sulfides and oxides are byproducts of the steel manufacturing process. For more than half a century, researchers have observed microstructural alterations around the inclusions commonly referred to as “butterfly wings.” This paper proposes a model to describe butterfly wing formation around nonmetallic inclusions. A 2D finite element model is developed to obtain the stress distribution in a domain subject to Hertzian loading with an embedded nonmetallic inclusion. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…41 These studies focused on modeling stress distribution, fatigue life, and fatigue indicator parameter. For example, Moghaddam et al 40,49 studied the WEA damage through 2D and 3D finite element model based on continuum damage mechanics. It was reported that the reciprocating shear stress is the main driving force of butterfly formation compared to the mean shear stress.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…41 These studies focused on modeling stress distribution, fatigue life, and fatigue indicator parameter. For example, Moghaddam et al 40,49 studied the WEA damage through 2D and 3D finite element model based on continuum damage mechanics. It was reported that the reciprocating shear stress is the main driving force of butterfly formation compared to the mean shear stress.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The effect of the mean stress cannot be neglected because the stress disturbance around the inclusion is asymmetrical. To incorporate the effects of both the mean stress and the stress amplitude during the rolling contact process, the equivalent stress is represented by [32]:…”
Section: Damage Evolutionmentioning
confidence: 99%
“…Cerullo and Tvergaard [31] obtained the stress field surrounding the inclusion and evaluated the contact fatigue using the DangVan multiaxial criterion. Moghaddam et al [32,33] investigated the formation of butterflies based on a FEM model and continuum damage mechanics (CDM). Guan et al [34] studied the crack nucleation and propagation induced by metallic carbides using the Voronoi finite element model.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusions in steel play a significant role in crack initiation, and the appearance of WECs is affected by inclusion types [22,24,25,39,40,48,49,70,71,73,74,[88][89][90]. Among all kinds of inclusions, MnS is more probable to induce WECs [35,49,71].…”
Section: Wecsmentioning
confidence: 99%